Determining Caffeine in Fat-Burning Supplements Using Thin Layer Chromatography-Densitometry and UV-Vis Spectrophotometer - Muhammad Luthfi Maulana; Muhammad Theza Ghozali (Journal of Fundamental and Applied Pharmaceutical Science, 2020)
There are so many ways to lose weight, such as consuming fat burner supplements to burn fat faster. A fat burner supplement consists of various ingredients, such as caffeine. Fat burner supplements are usually not registered in BPOM RI. This study aims to evaluate caffeine in fat burner supplements qualitatively and quantitatively. These supplements were analyzed in the pharmaceutical laboratory in Universitas Muhammadiyah Yogyakarta using Thin Layer Chromatography (TLC)–Densitometry and UV–Vis Spectrophotometer. Sample preparation was conducted by separating caffeine from supplements by a separatory funnel with chloroform as an organic solvent. Qualitative analysis was carried out by TLC and analyzing standard spectrum, and sampling technique was carried out with UV–Vis Spectrophotometer. The first quantitative analysis used densitometry by measuring the spot on the TLC plate. Meanwhile, the second quantitative analysis used UV–Vis Spectrophotometer by observing absorbency value on samples with λ 273.5 nm. The result of the qualitative test using TLC was analyzed by comparing the Rf value of the standard and the sample. The Rf value of caffeine standard was 0.63, and every sample showed similar value with caffeine standard, indicating that all samples contain caffeine. The result of quantitative test with TLC - Densitometry method revealed 1st sample 5.68 mg/ml, 2nd sample 5.74 mg/ml, 3rd sample 3.43 mg/ml, 4th sample 8.90 mg/ml, and 5th sample 1.88 mg/ml. The qualitative test result was analyzed using the UV–Vis Spectrophotometer method, and all of the caffeine standard spectra can be read at wavelength 273.5 nm, which means all samples contain caffeine. The second quantitative test result analyzed by using UV–Vis Spectrophotometer method  showed 1st sample 3.22 mg/g, 2nd sample 4.56 mg/g, 3rd sample 2.23 mg/g, 4th sample 11.22 mg/g, and 5th sample 0.26 mg/g. It can be concluded that all samples (fat burners) contained caffeine.